Lesser Known Large dsDNA Viruses - Takahashi, Shin (Springer, 2017)
Preface -- The Phycodnaviridae. The story of how tiny giants rule the world -- Mimivirus -- Family Iridoviridae. Poor viral relations no longer -- African swine fever virus -- Ascoviruses -- Whispovirus -- Jumbo bacteriophages -- Subject index.